Understanding Turkish students' STEM career aspirations, STEM hopes and goals, parental perception, and cultural capital: A path analysis - Hakan Ulum; Menşure Alkış Küçükaydın (STEM Education)
Developing students' career goals in science, technology, engineering, and mathematics (STEM) is a high priority in Turkey and around the world. Many educational investments are being made in the country, as shown in the development goals. It is important to understand the variables that may be related to these goals to best support students on their career path. We examined the relationships between STEM career aspirations, hopes, and goals in STEM, cultural capital, and perceived parental expectations in a Turkish sample (n = 633). The findings showed positive relationships between STEM cultural capital, perceived parental support, and STEM-related hopes and goals. In addition, parental perception influenced STEM career aspirations both directly and indirectly. In the research model, the greatest effect was between parental support and STEM hopes and goals. These discoveries provide insight for educational policymakers, parents, and teachers who are helping students develop STEM career aspirations.